Classi medie nei Paesi emergenti - Bianco, Adele (SocietàMutamentoPolitica, 2013)
This paper aims at analyzing the emergence of the middle classes in BRIC(S) countries. Despite the differences between the geo-cultural contexts, it is a phenomenon that goes hand in hand with extremely significant growth rates experienced by emerging economies over the last decade. Dealing with the specific characteristics of the middle classes in BRIC(S) countries means facing with a matter of the global future in terms of both economic prospects and international relationship. In this paper we are going to reconstruct firstly an operational definition of middle class concept in emerging economies, as well as defining criteria and drafting their future evolution. Secondly we are going to examine the articulation of the middle class in each BRIC(S) countries (Asia, South America and the Caribbean, Africa, Russia). Finally, we are going to mention the social policies necessary to maintain and develop the standard of living achieved: public expenditures in health and education as well as infrastructural investment.